The Effect of Digital Competence and Psychological Well-Being on Career Choices through Self-Efficacy among MPLB Students - Almeida Rohma Safitri; Triesninda Pahlevi (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study analyzes the influence of digital competence and psychological well-being on career choices through self-efficacy among students in the Office Management and Business Services (MPLB) program. A quantitative explanatory approach forms the basis of this research. From a population of 148 students, the Slovin formula and proportional stratified random sampling determined a sample of 108 respondents. Data collection utilized a Likert-scale questionnaire, and analysis employed the PLS-SEM method with SmartPLS. The results indicate that digital competence and psychological well-being positively and significantly affect self-efficacy and career choice. Self-efficacy also plays a significant mediating role in these relationships, with psychological well-being emerging as the most dominant factor.